THE NATURE OF HUMAN MISERING IN SURAH AL-MA'ARIJ VERSES 19-21 MAQASHIDI INTERPRETATION APPROACH - Syukri Daud; Hikmatul Hayati; Meinisa Farhani; Bayu Alam Ardiansyah; Syahidatul Nabila (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2025)
This study is entitled "The Miserly Nature of Humans in Surah Al-Ma’arij Verses 19–21: A Maqashidi Tafsir Approach". The focus of this research is to uncover the essence of human miserliness as described in Surah Al-Ma’arij verses 19–21 and to explore its relevance in religious and social life using the Maqashidi interpretation approach. The choice of this topic is based on the reality that miserliness is one of the spiritual diseases that hinders social justice and public welfare. This study uses a qualitative method with a library research approach and applies Maqashidi exegesis to extract the values of maqashid al-shari’ah (objectives of Islamic law) embedded in the verses. The findings show that humans are innately anxious and miserly, except for those who are faithful, perform prayer regularly, and are consistent in righteous deeds. These verses highlight the significance of spiritual development in overcoming greed and emphasize Islam’s concern for social justice and solidarity. The conclusion of this research underlines that miserliness is a moral problem that can be addressed through the maqashidi framework by strengthening faith, worship, and social awareness. The study recommends the implementation of value-based character education inspired by maqashid principles to cultivate generous and socially responsible individuals.